Synergistic antifungal effects and mechanisms of amantadine hydrochloride combined with azole antifungal drugs on drug-resistant Candida albicans - Li, Xiuyun; Zhi, Yuanyuan; Duan, Ximeng; Chen, Xu; Cui, Min; Zheng, Shicun (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe increasing resistance of Candida albicans (C. albicans) to conventional antifungal drugs poses a great challenge to the clinical treatment of infections caused by this yeast. Drug combinations are a potential therapeutic approach to overcome the drug- resistance of C. albicans. This study explored the synergistic effects of amantadine hydrochloride (AMH) combined with azole antifungal drugs against drug-resistant C. albicans in vitro and in vivo.MethodsThe in vitro sensitivity of Candida spp. to drugs was determined by the microdilution method. The effect of drugs on the efflux pump activity of C. albicans was determined by the rhodamine 6G tracer method. The egg yolk agar plate method was used to determine the activity of extracellular phospholipase, a C. albicans virulence factor. The Galleria mellonella model of C. albicans infection was used to test the in vivo efficacy of the combination therapy.ResultsIn vitro experiments showed that combinations of AMH with azole antifungal drugs had synergistic antifungal effects on planktonic cells of drug-resistant C. albicans, with fractional inhibitory concentration index values of <0.5. The in vivo synergistic effects and mechanism of drug combinations with AMH were further studied using fluconazole (FLC) as a representative azole antifungal drug. In vivo, G. mellonella larvae were used to evaluate the antifungal efficacy of AMH +FLC. AMH + FLC treatment increased the survival rate of larvae infected with drug-resistant C. albicans and reduced tissue invasion. Studies of the mechanism of synergy showed that AMH inhibited drug efflux pump activity in drug-resistant C. albicans, and that AMH + FLC synergistically inhibited early biofilms and the extracellular phospholipase activity of drug-resistant C. albicans.ConclusionThis study provides strong evidence that combinations of non-antifungal drugs and antifungal drugs can effectively overcome drug-resistant C. albicans infection. Both AMH and FLC are FDA-approved drugs, eliminating concerns about safety. Our findings provide a foundation for further clinical antifungal research.